Characteristics of Eulerian mesoscale eddies in the Gulf of Mexico - Zhu, Yingli; Liang, Xinfeng (Frontiers in Marine Science, 2022)
Although numerous studies on Eulerian mesoscale eddies with closed contours of sea surface height (SSH) or streamline have been conducted in the Gulf of Mexico (GoM), a comprehensive study on their temporal and spatial characteristics is still lacking. In this study, we combine three eddy detection algorithms to detect Eulerian eddies from the 26-year SSH record in the GoM and examine their characteristics. We find distinct characteristics between Loop Current Eddies (LCEs), Loop Current Frontal Eddies (LCFEs), and mesoscale eddies that are not directly related to the Loop Current (LC). Many characteristics of LCEs and LCFEs in the eastern GoM are closely related to the LC. More LCFEs are formed in January to July than in August to December, likely related to the seasonal variation of the northward penetration of the LC. However, the formation of non-LCFE cyclonic eddies shows a biannual variability, which could be linked to the position and strength of the background current in the western GoM. Nevertheless, the seasonal variability of the Eulerian eddies shows large uncertainties (not significant at the 95% confidence level). Low-frequency (interannual to multidecadal) variability is also detected. In the eastern GoM, the extent of northward penetration of the LC can affect the generation of LCFEs and result in low-frequency variations. In the western GoM, the low-frequency variability of eddy occurrence and amplitude could be related to the surface circulation strength.